Similar hydraulic efficiency and safety across vesselless angiosperms and vessel-bearing species with scalariform perforation plates. (28th March 2019) - Trueba, Santiago; Delzon, Sylvain; Isnard, Sandrine; Lens, Frederic
Abstract : Xylem hydraulic conductivity and embolism vulnerability are similar between vesselless and vessel-bearing angiosperm species. Significant differences in vulnerability to embolism across species are explained by interconduit pit membrane thickness. Abstract: The evolution of xylem vessels from tracheids is put forward as a key innovation that boosted hydraulic conductivity and photosynthetic capacities in angiosperms. Yet, the role of xylem anatomy and interconduit pits in hydraulic performance across vesselless and vessel-bearing angiosperms is incompletely known, and there is a lack of functional comparisons of ultrastructural pits between species with different conduit types. We assessed xylem hydraulic conductivity and vulnerability to drought-induced embolism in 12 rain forest species from New Caledonia, including five vesselless species, and seven vessel-bearing species with scalariform perforation plates. We measured xylem conduit traits, along with ultrastructural features of the interconduit pits, to assess the relationships between conduit traits and hydraulic efficiency and safety. In spite of major differences in conduit diameter, conduit density, and the presence/absence of perforation plates, the species studied showed similar hydraulic conductivity and vulnerability to drought-induced embolism, indicating functional similarity between both types of conduits. Interconduit pit membrane thickness ( T m ) was the only measured anatomical feature that showed a relationship to significant vulnerability to embolism. Our results suggest that the incidence of drought in rain forest ecosystems can have similar effects on species bearing water-conducting cells with different morphologies.